Whole-genome analysis of dorsal-ventral patterning in the Drosophila embryo. - Stathopoulos, A.; Van Drenth, M.; Erives, A.; Markstein, M.; Levine, M. (Cell, 2002)
The maternal Dorsal regulatory gradient initiates the differentiation of several tissues in the early Drosophila embryo. Whole-genome microarray assays identified as many as 40 new Dorsal target genes, which encode a broad spectrum of cell signaling proteins and transcription factors. Evidence is presented that a tissue-specific form of the NF-Y transcription complex is essential for the activation of gene expression in the mesoderm. Tissue-specific enhancers were identified for new Dorsal target genes, and bioinformatics methods identified conserved cis-regulatory elements for coordinately regulated genes that respond to similar thresholds of the Dorsal gradient. The new Dorsal target genes and enhancers represent one of the most extensive gene networks known for any developmental process.